Analisis Strategi Pemasaran dalam Meningkatkan Penjualan Pestisida (insektisida) pada PT Kimika Usaha Prima - Iqbal Asyraf Dzaky; Wasti Reviandani (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2025)
The research focuses on analyzing the sales marketing strategy of PT Kimika Usaha Prima company to find alternative marketing strategies to the problems faced. The research uses a qualitative descriptive method to describe the problem and the information obtained during the research process. The research analysis tool uses SWOT Analysis to identify internal factors (strengths and weakness) and external factors (opportunities, and threat) in PT Kimika Usaha Prima. The results of the SWOT analysis will be in the form of several alternative options for marketing strategies that aim to increase sales of insecticide pesticides. The results of the study show that the company PT Kimika Usaha Prima needs to plan and implement alternative marketing strategies by conducting seasonal promotions on superior products, expanding online promotion efforts, organizing product trials, and product diversification to customers.